การศึกษาแบบจำลองเชิงสาเหตุของพฤติกรรมการบริโภคด้วยปัญญาของนักเรียน ประถมศึกษาปีที่ 6 โรงเรียนสังกัดสำนักงานเขตกรุงเทพมหานคร - (อชิโต) PhrmahaSupachaiSaetier (Achito), พระมหาศุภชัย แซ่เถียร; อินทรกำแหง (Ungsinun Intarakamhang), อังศินันท์ (Journal of Behavioral Science for Development, 2016)
(THE CAUSAL MODEL STUDY OF INTELLIGENT CONSUMPTION BEHAVIORS FOR GRADE 6 STUDENSTS UNDER THE DEPARTMENT OF BANGKOK METROPOLITAN) Abstract The purpose of this study were to develop the causal model and to find out the important causal variables effect size influencing to intelligent consumption behaviors for grade 6 students. The three stage sampling of 654 students. Descriptive statistics were analyzed by statistical package and the hypothesized models were examined by LISREL. The findings were as follows: 1) The hypothesized causal model of intelligent consumption behaviors are in harmony with the empirical data after adjusted model resulting in the satisfactory level of goodness of fitting indices with X2= 219.45, df = 93,p = .00,X2/df = 2.35, SRMR = .048, RMSEA = .049, GFI = .95, AGFI = .93, NFI = .97, CFI = .98, PNFI = .75, PGFI = .67 2) Students’ Yonisomanasikarn had direct effect on intelligent consumption behaviors 3) Family influence had direct effect on Yonisomanasikarn with intelligent consumption behaviors and had indirect effect on intelligent consumption behaviors through Yonisomanasikarn 4) Kalayanamitt influence with Mass media influence had direct effect on Yonisomanasikarn and had indirect effect on intelligent consumption behaviors through Yonisomanasikarn but did not have direct effect on intelligent consumption behaviors. Keyword: Intelligent consumption behaviors Yonisomanasikarn Family influence